Determination of Nitrates, Nitrites and Oxalates in Kale and Sultana Pea by Capillary Electrophoresis - Erdoǧan, B.Y.; Nur Onar, A.N. (Bureau Food Drug Analysis, 2012)
The objective of this research was to determine the concentrations of nitrate, nitrite and oxalate in two vegetables which are popular at Black Sea coast, namely kale (5. oleracea var. acephala) and sultana pea (Pisum sativum var. saccharatum). The results were compared with the concentrations in spinach and chard. Simultaneous determination of nitrate, nitrite and oxalate was conducted by capillary electrophoresis using an acidic run buffer to reverse the electroosmotic flow. Full factorial design was applied to optimize the capillary electrophoretic experimental conditions. For this purpose, eight randomized experiments were conducted using three variables with two levels: pH (2.5-3.5), temperature (23-30°C) and applied voltage (-(15-20) kV). The limit of detection was improved using large volume sample stacking. The average amount of nitrate in fresh kale leaves (2016 ± 519 mg/kg) was greater than that in spinach and lower than that in chard. The nitrite ion concentrations were much more in the leaves of kale (111 ± 4 mg/kg) than in stalks on the contrary of chard. Oxalate concentration was lower in kale (2970 ± 672 mg/kg) than in spinach and chard.
Keywords: Electroosmotic Flow Reversal; Kale; Nitrate; Nitrite; Oxalate; Sultana Pea